Mapping the OECD Government Procurement Taxonomy with International Best Practices An Implementation to ASEAN Countries - Gourdon, Julien (OECD Publishing, 2018)
The OECD developed a taxonomy of measures affecting government procurement which provides a classification system for different GP measures, policies and procedures, which can impact cross-border government procurement. This project aims to further assist countries in assessing their procurement regimes by mapping the taxonomy against international good practices. The project maps the taxonomy against both the WTO Government Procurement Agreement and the UNCITRAL Model Law on Public Procurement (2011). It further tests this methodology with data collection in four ASEAN countries (Indonesia, Malaysia, Philippines and Viet Nam)
Keywords: Trade